Ivabradine for the Prevention of Anthracycline-Induced Cardiotoxicity in Female Patients with Primarily Breast Cancer: A Prospective, Randomized, Open-Label Clinical Trial - Eglė Čiburienė; Sigita Aidietienė; Greta Ščerbickaitė; Eglė Sadauskienė; Diana Sudavičienė; Edita Baltruškevičienė; Birutė Brasiūnienė; Monika Drobnienė; Jelena Čelutkienė (Medicina, 2023)
Background and Objectives: Cancer therapy containing anthracyclines is associated with cancer-treatment-related cardiac dysfunction and heart failure (HF). Conventional cardioprotective medications can be frequently complicated by their blood-pressure-lowering effect. Recently, elevated resting heart rate was shown to independently predict mortality in patients with cancer. As a heart rate-lowering drug without affecting blood pressure, ivabradine could present an alternative management of anthracyclines-induced cardiotoxicity. Materials and Methods: This study aimed to investigate the probable protective effects of ivabradine in cancer patients with elevated heart rate (>75 beats per minute) undergoing anthracycline chemotherapy. Patients referred by oncologists for baseline cardiovascular risk stratification before anthracycline chemotherapy who met the inclusion criteria and had no exclusion criteria were randomly assigned to one of two strategies: ivabradine 5 mg twice a day (intervention group) or controls. Electrocardiogram, transthoracic echocardiogram with global longitudinal strain (GLS), troponin I (Tn I), and N-terminal natriuretic pro-peptide (NT-proBNP) were performed at baseline, after two and four cycles of chemotherapy and at six months of follow-up. The primary endpoint was the prevention of a >15% reduction in GLS. Secondary endpoints were effects of ivabradine on Tn I, NT-proBNP, left ventricular (LV) systolic and diastolic dysfunction, right ventricle dysfunction, and myocardial work indices. Results: A total of 48 patients were enrolled in the study; 21 were randomly assigned to the ivabradine group and 27 to the control group. Reduced GLS was detected 2.9 times less often in patients receiving ivabradine than in the control group, but this change was non-significant (OR [95% CI] = 2.9 [0.544, 16.274], p = 0.208). The incidence of troponin I elevation was four times higher in the control group (OR [95% CI] = 4.0 [1.136, 14.085], p = 0.031). There was no significant change in NT-proBNP between groups, but the increase in NT-proBNP was almost 12% higher in the control group (OR [95% CI] = 1.117 [0.347, 3.594], p = 0.853). LV diastolic dysfunction was found 2.7 times more frequently in the controls (OR [95% CI] = 2.71 [0.49, 15.10], p = 0.254). Patients in the ivabradine group were less likely to be diagnosed with mild asymptomatic CTRCD during the study (p = 0.045). No differences in right ventricle function were noted. A significant difference was found between the groups in global constructive work and global work index at six months in favour of the ivabradine group (p = 0.014 and p = 0.025). Ivabradine had no adverse effects on intracardiac conduction, ventricular repolarization, or blood pressure. However, visual side effects (phosphenes) were reported in 14.3% of patients. Conclusions: Ivabradine is a safe, well-tolerated drug that has shown possible cardioprotective properties reducing the incidence of mild asymptomatic cancer-therapy-induced cardiac dysfunction, characterised by a new rise in troponin concentrations and diminished myocardial performance in anthracycline-treated women with breast cancer and increased heart rate. However, more extensive multicentre trials are needed to provide more robust evidence.